Strategi Pengendalian Banjir Sungai Banger Kota Pekalongan terhadap Penurunan Muka Tanah dan Kenaikan Muka Laut - Gilang Alfajar; Arno Adi Kuntoro; Nur Laili Yasinta; Irfie Lutfiah Aulia Rahman; Eka Oktariyanto Nugroho; Imron Rosyidi; Sella Lestari Nurmaulia; Mohammad Iqbal Huseiny (JURNAL TEKNIK HIDRAULIK, 2025)
Pekalongan City, located on the northern coast of Central Java, is vulnerable to flooding due to high rainfall, low land elevation, land subsidence, sea level rise, and uncontrolled human activities. The Banger River, originally constructed as an artificial river to reduce flooding from the Loji River, has now become a source of flooding. This study aims to identify technical flood control solutions for the Banger River using spatial, hydrological, tidal, and hydraulic analyses supported by hydraulic flow modeling software. Twenty years of rainfall data, spatial data, river geometry, and tidal information were used to simulate existing and projected long-term conditions. The design flood discharge with a 20-year return period was calculated at 281,9 cubic meters per second, resulting in an average inundation of 0,27 meters, which may rise to 0,85 meters within the next ten years due to land and sea level changes. Three alternatives were evaluated: normalization with earth embankment, a combination of normalization and parapet, and parapet-only implementation. Results indicate that using parapets, or combining them with river normalization and embankments, offers the most technically effective flood control solution in both short and long terms. Overall, the study emphasizes the need for adaptive flood management strategies in coastal urban areas. It is recommended that local governments integrate structural measures with nonstructural policies, such as land use regulation and public awareness, to ensure sustainable flood risk reduction.